Predicting method on settlement of soft subgrade soil caused by traffic loading involving principal stress rotation and loading frequency - Wu, Tingyu; Jin, Hongxu; Guo, Lin; Sun, Honglei; Tong, Junhao; Jiang, Yaochen; Wei, Pengfei (Soil dynamics and earthquake engineering (1984), 2022)
Since the alarming settlement of transport infrastructures on soft subgrade caused by long-term traffic loading, a method for predicting settlement is of considerable significance in the engineering design. In this study, we proposed a practical and simple predicting method on the settlement of soft subgrade considering traffic loading effects. The model used in this method involves the principal stress rotation and loading frequency, which needs only four parameters with clear meaning obtained by several cyclic triaxial tests. The applicability of the model has been verified by previous results from other researchers. Moreover, the engineering practicality of this method was validated by the field data of a highway. The settlements under low-frequency and high-frequency are the upper limit and lower limit of the traffic load-induced settlements, respectively. With the increasing embankment thickness, the settlements decrease because the cyclic stress ratio decreases and the detrimental effect of the principal stress rotation on the settlement reduces. The vehicle load is a more influential factor in the settlement than the traffic volume. •Develop a new empirical model on permanent strain considering PSR and f.•The model parameters with clear meaning can be determined by only 4 CT tests.•The calculation with this model agrees well with the field settlement.•The embankment thickness, vehicle speed, and load affect the settlement most.